2020
DOI: 10.1155/2020/2743060
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Diagnosis of Gastric Cancer by Magnetic Beads Extraction and Mass Spectrometry

Abstract: Objective. This study constructed a model for the early diagnosis of gastric cancer by comparing the serum peptides profiles of patients with advanced gastric cancer and healthy people. And that model may be the potential to be applied for the efficacy evaluation and recurrence monitoring in gastric cancer. Methods. Serums of 30 healthy people and 30 advanced gastric cancer patients were matched by age and gender were collected. The serum peptide spectrum was obtained by MB-WCX concentration and MALDI-TOF MS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Similarly, the MP3C has collaborated with community organizations and leaders to ensure an increase in the number of community health workers and patient navigators, who have been trained to ensure care access increases. Community awareness concerning resources for no-cost or low-cost cancer screening services has been promoted, with underserved neighborhoods particularly targeted in Mississippi [ 17 , 18 ]. The initiatives have been completed by collaboration with community and faith organizations, translating to culturally appropriate and comprehensive gastric cancer education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the MP3C has collaborated with community organizations and leaders to ensure an increase in the number of community health workers and patient navigators, who have been trained to ensure care access increases. Community awareness concerning resources for no-cost or low-cost cancer screening services has been promoted, with underserved neighborhoods particularly targeted in Mississippi [ 17 , 18 ]. The initiatives have been completed by collaboration with community and faith organizations, translating to culturally appropriate and comprehensive gastric cancer education.…”
Section: Discussionmentioning
confidence: 99%
“…The initiatives have been completed by collaboration with community and faith organizations, translating to culturally appropriate and comprehensive gastric cancer education. Still, the number of health and wellness initiatives has increased in Mississippi, ensuring early detection is increased by as high as 25% [ 18 ]. Across the state, therefore, the MP3C has conducted environmental scans to uncover current ministerial alliances, faith-related associations and groups, and health ministries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent publication screened 11 differentially expressed proteins from GC plasma samples as early diagnostic biomarkers for GC [82]. Alternatively, MS-based analysis of GC cancerous and normal serum has shown that peaks at 2953 and 1945 Da have higher specificity and sensitivity than traditional CEA and CA19-9 biomarkers in GC diagnosis [83]. Another recent study proposed that DEK proteins might be used as novel biomarkers for GC [84] finding that the plasma content of DEK also reached superior sensitivity compared to the traditional biomarkers CEA, CA19.9.…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%
“…There are several types of magnetic beads, such as the weak cation exchange (WCX) type, weak anion exchange (WAX) type, hydrophobic interaction of carbon binding group type (e.g., C3, C8, and C18), immobilized metal ion affinity chromatograph with Cu(2+) or Fe(3+) (IMAC-Cu, Fe) type, and immunoaffinity chromatography on immobilized protein G (IAC Prot G) type ( 9 ). Bioactive substances can be fixed to magnetic beads, which have large surface areas and can capture small peptides and proteins ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%